Cardiac catheterization and complications: initial experience - Dubey, L; Sharma, SK (Journal of College of Medical Sciences-Nepal, 2012)
Cardiac catheterization for diagnostic and therapeutic purposes has been routinely used since last one year in College of Medical Sciences and Teaching Hospital, Bharatpur, Nepal. Because all cardiac catheterizations involve the insertion of cardiac catheters into the circulatory system, it should not be surprising that a variety of complications can ensue. These complications range from minor problems with no long-term sequelae to major problem even death. A total of 357 consecutive diagnostic and therapeutic cardiac catheterization performed in College of Medical Sciences and Teaching Hospital, Bharatpur between April 2011 to April 2012 were evaluated for their complications. Among them 220 (61.6%) were coronary angiogram, 65 (18.2 %) percutaneous transluminal coronary angioplasty (PTCA) and stenting, 7 ( 1.9 %) permanent pacemaker insertion, 65 (18.2%) were others including temporary pacemaker insertion, peripheral angiography and carotid angiography. There were 3 deaths (0.84%). Two deaths occurred following coronary angiogram and 1 death following PTCA stenting. Vascular complications occurred in 5 (1.4% patients) with groin haematoma in all. Contrast allergy occurred in 9 (2.5 %), vasovagal reaction in 2 (0.56%), pyrogen reaction in 6 (1.6%), and contrast induced nephropathy occurred in 3 (0.84%) patients. Cardiac catheterization procedure in CMS-TH, Bharatpur has acceptable low complications including death. Journal of College of Medical Sciences-Nepal,2012,Vol-8,No-2, 1-6 DOI: http://dx.doi.org/10.3126/jcmsn.v8i2.6830